ROUTES OF MANAGERIAL APPROACH IN SANSKRIT LITERATURE – WITH SPECIAL REFERENCE TO BHAGAVAD GITA - Tripathi, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian knowledge system has a prominence place in the modern management. Whatever we are acquiring in today’s corporate world, all are grounded on Indian Ethos. This article is erected on the study of Sanskrit literature “Shri Bhagavad Gita” and its distinguished place in modern era of management. Modern visionary perspective, meditation /Samatvam yogah uchyate), duty /Nishkaam karma /kartvya and knowledge gyaan, assistance the manager to explore the numerous opportunities accessible in the present time of life and work as a global leader.